Dietary Nitrate Intake Is Positively Associated with Muscle Function in Men and Women Independent of Physical Activity Levels. Issue 5 (24th March 2021) - Sim, Marc; Blekkenhorst, Lauren C; Bondonno, Nicola P; Radavelli-Bagatini, Simone; Peeling, Peter; Bondonno, Catherine P; Magliano, Dianna J; Shaw, Jonathan E; Woodman, Richard; Murray, Kevin; Lewis, Joshua R; Daly, Robin M; et al.
ABSTRACT: Background: Nitrate supplements can improve vascular and muscle function. Whether higher habitual dietary nitrate is associated with better muscle function remains underexplored. Objective: The aim was to examine whether habitual dietary nitrate intake is associated with better muscle function in a prospective cohort of men and women, and whether the relation was dependent on levels of physical activity. Methods: The sample ( n = 3759) was drawn from the Australian Diabetes, Obesity, and Lifestyle Study (AusDiab) (56% female; mean ± SD baseline age: 48.6 ± 11.1 y). Habitual dietary intake was assessed over 12 y by obtaining an average [of at least 2 time points, e.g., baseline (2000/2001) and 2004/2005 and/or 2011/2012] from a food-frequency questionnaire. Nitrate intake was calculated from a validated nitrate database and other published literature. Muscle function was quantified by knee extension strength (KES) and the 8-ft-timed-up-and-go (8ft-TUG) test performed in 2011/2012. Physical activity was assessed by questionnaire. Generalized linear models and logistic regression were used to analyze the data. Results: Median (IQR) total nitrate intake was 65 (52–83) mg/d, with ∼81% derived from vegetables. Individuals in the highest tertile of nitrate intake (median intake: 91 mg/d) had 2.6 kg stronger KES (11%) and 0.24 s faster 8ft-TUG (4%) compared with individuals in the lowest tertile of nitrate intake (median intake: 47 mg/d; both P < 0.05). Similarly, individuals in the highest tertile of nitrate intake had lower odds for weak KES (adjusted OR: 0.69; 95% CI: 0.47, 0.73) and slow 8ft-TUG (adjusted OR: 0.63; 95% CI: 0.50, 0.78) compared with those in the lowest tertile. Physical activity did not influence the relationship between nitrate intake and muscle function (KES; P- interaction = 0.86; 8ft-TUG; P- interaction = 0.99). Conclusions: Higher habitual dietary nitrate intake, predominantly from vegetables, could be an effective way to promote lower-limb muscle strength and physical function in men and women.